Big graph visual analytics. (July 2017) - Haglin, David; Trimm, David; Wong, Pak Chung
This special issue of Information Visualization explores the technical challenges and technology development opportunities of graph visual analytics arising from the trend of big data. Big graph visual analytics is about applying visualization and analytics techniques to gather, analyze, and understand big graphs and the knowledge behind them.